The Bear Grylls Adventure. Book 7, The Volcano Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
The seventh in the exciting new 12-book collectible series for young readers from survival expert and Chief Scout Bear Grylls. Each book follows a different child on the outdoor activity camp. Once they are given the magical compass, they meet the inspirational adventurer in an amazing place and learn new skills and facts they can take with them back to their real life.